PROTECTION OF CHILDREN’S RIGHTSIN THE PROCESS OF MEDIA COVERAGE - Petrosyan, Rubina (State and Law, 2026)
As a result of various global changes and the widespread expansion of digital media, the activity of family influencers on social media has evolved into a multi-billion-dollar industry, often centered around children. Lacking a clearly defined legal status and excluded from negotiating or consenting to either labor or civil contracts, children ultimately become the performers or service providers under such agreements. This article analyzes the concept of “sharenting” and its potential dangers, including identity theft, psychological harm, and the deprivation of a child’s ability to shape their own identity. Within the boundaries of parental autonomy, the article proposes the legal recognition of a child’s “right to be forgotten,” enabling individuals, upon reaching adulthood, to request the removal of their images and personal information from monetized content. This approach aims to protect both parental rights and reduce the long-term risks of exploitation and harm to children.
Keywords: Children’s rights; Monetized content; Influencer; Sharenting; Right to be forgotten; Social media; Personal data protection; Identity theft; Parental autonomy